2015
DOI: 10.1016/j.tsf.2015.11.046
|View full text |Cite
|
Sign up to set email alerts
|

Impact of surface interactions on the phase behavior of Y-shaped molecules

Abstract: In recent years the statistical mechanics of non-spherical molecules, such as polypeptide chains and protein molecules, has garnered considerable attention as their phase behavior has important scientific and health implications. One example is provided by immunoglobulin, which has a "Y"-shape. In this work, we determine the phase diagram of Y-shaped molecules on a hexagonal lattice through Monte Carlo Grand Canonical ensemble simulation, using histogram reweighting, multicanonical sampling, and finite-size sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…In this paper, we determine the different phases and nature of the phase transitions when only excluded volume interactions are present, corresponding to the infi-arXiv:1712.02301v1 [cond-mat.stat-mech] 6 Dec 2017 nite temperature limit of the model studied in Refs. [25,26]. We show that the sublattice phase at high densities which breaks particle symmetry is unstable to a sliding instability in the presence of vacancies.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…In this paper, we determine the different phases and nature of the phase transitions when only excluded volume interactions are present, corresponding to the infi-arXiv:1712.02301v1 [cond-mat.stat-mech] 6 Dec 2017 nite temperature limit of the model studied in Refs. [25,26]. We show that the sublattice phase at high densities which breaks particle symmetry is unstable to a sliding instability in the presence of vacancies.…”
Section: Introductionmentioning
confidence: 83%
“…The high density phase that we observe in this paper has columnar order with both types of particles equally present, which is in contradiction to the results obtained from Monte Carlo simulations of Y -shaped particles with attractive interactions in Refs. [25,26], wherein it was shown that the high density phase has sublattice order in which only one kind of particle is present. For only ex-cluded volume interactions, we argued in Sec.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations